Rigorous Software Engineering for Service-Oriented Systems Results of the SENSORIA Project on Software Engineering for Service-Oriented Computing - Wirsing, Martin; Hölzl, Matthias; SpringerLink (Online service). (2011)
Service-Oriented Computing is a paradigm for developing and providing software that can address many IT challenges, ranging from integrating legacy systems to building new, massively distributed, interoperable, evaluable systems and applications. The widespread use of SOC demonstrates the practical benefits of this approach. Furthermore it raises the standard for reliability, security, and performance for IT providers, system integrators, and software developers. This book documents the main results of Sensoria, an Integrated Project funded by the European Commission in the period 2005-2010. The book presents, as Sensoria's essence, a novel, coherent, and comprehensive approach to the design, formal analysis, automated deployment, and reengineering of service-oriented applications. Following a motivating introduction, the 32 chapters are organized in the following topical parts: modeling in service-oriented architectures; calculi for service-oriented computing; negotiation, planning, and reconfiguration; qualitative analysis techniques for SOC; quantitative analysis techniques for SOC; model-driven development and reverse engineering for service-oriented systems; and case studies and patterns.
SENSORIA - Software Engineering for Service-Oriented Overlay Computers -- A Unifying Formal Basis for the SENSORIA Approach: A White Paper -- Introduction to the SENSORIA Case Studies -- UML Extensions for Service-Oriented Systems -- The SENSORIA Reference Modeling Language -- Model-Driven Development of Adaptable Service-Oriented Business Processes -- A Formal Support to Business and Architectural Design for Service-Oriented Systems -- Core Calculi for Service-Oriented Computing -- Behavioral Theory for Session-Oriented Calculi -- Static Analysis Techniques for Session-Oriented Calculi -- Call-by-Contract for Service Discovery, Orchestration and Recovery.-CC-Pi: A Constraint Language for Service Negotiation and Composition -- Advanced Mechanisms for Service Composition, Query and Advanced Mechanisms for Service Combination and Transactions -- Model-Driven Development of Long Running Transactions -- Hierarchical Models for Service-Oriented Systems -- Analysing Protocol Stacks for Services -- An Abstract, on the Fly Framework for the Verification of Service-Oriented Systems.-Tools and Verification -- Specification and Analysis of Dynamically-Reconfigurable Service Architectures -- SoSL: A Service-Oriented Stochastic Logic -- Evaluating Service Level Agreements Using Observational Probes -- Scaling Performance Analysis Using Fluid-Flow Approximation -- Passage-End Analysis for Analysing Robot Movement -- Quantitative Analysis of Services -- Methodologies for Model-Driven Development and Deployment: An Overview -- Advances in Model Transformations by Graph Transformation: Specification, Execution and Analysis.-Runtime Support for Dynamic and Adaptive Service Composition.-Legacy Transformations for Extracting Service Components.-The SENSORIA Development Environment -- Specification and Implementation of Demonstrators for the Case Studies -- SENSORIA Results Applied to the Case Studies -- Analysing Robot Movement Using the SENSORIA Methods -- The SENSORIA Approach Applied to the Finance Case Study -- SENSORIA Patterns.
Electronic reproduction.
Keywords: SENSORIA Project; Service-oriented architecture (Computer science).; Web services; Electronic books